Profiling and hormonal therapy for acne in women - Sangita Ghosh; Soumik Chaudhuri; Vijay Kumar Jain; Kamal Aggarwal (Wolters Kluwer Medknow Publications, 2014)
Acne vulgaris is the most common condition treated by physicians worldwide. Though most acne patients remit spontaneously, for the ones that do not or are unresponsive to conventional therapy or have obvious cutaneous signs of hyperandrogenism, hormonal therapy is the next option in the therapeutic ladder. It is not strictly indicated for only those patients who have cutaneous or biochemical evidence of hyperandrogenism, but can be used even without any evidence of hyperandrogenism, for therapy-resistant acne. It can be prescribed as monotherapy, but when used in combination with other conventional therapies, it may prove to be more beneficial. Hormonal evaluation is a prerequisite for hormonal therapy, to identify the cause behind hyperandrogenism, which may be ovarian or adrenal. This article reviews guidelines for patient selection and the various available hormonal therapeutic options, their side-effect profile, indications and contraindications, and various other practical aspects, to encourage dermatologists to become comfortable prescribing them.